Exploring the value of 'The Rwandan genocide Film' as a pedagogical tool for raising awareness - Adams, Khaya (Department of Historical Studies, 2020)
The Rwandan genocide is a complex subject that even works of written historical discourse struggle to explain. Previous filmic studies have primarily focused on three well known Rwandan genocide films, Hotel Rwanda, Shooting Dogs and Sometimes in April; this thesis expands its focus to nine feature films. Genocide films come under immense scrutiny when judged against the events they seek to represent. This scrutiny is accompanied with a misunderstanding of what exactly genocide films are. I will be looking at four thematic topics to alleviate this misunderstanding: how the films represent the history of Rwanda and the genocide; physical violence and death during the genocide; the female experience of the genocide, with an emphasis on sexual violence; and the abandonment of Rwanda by the West, with a focus on afro-pessimism. Through this analysis, I will argue for the value they possess as a medium in being able to not only raise awareness about the genocide, but to also convey salient information, to viewers. Films are not substitutes for written historical discourse but should rather be seen as supplementary educational tools used to enrich the existing canon of work. Once one understands the different judging criteria that should be afforded to genocide films, one will be able to recognise the value they possess.